Sources of tooth wear variation early in life among known‐aged wild ring‐tailed lemurs (Lemur catta) at the Bezà Mahafaly Special Reserve, Madagascar. Issue 11 (20th June 2014) - Cuozzo, Frank P.; Head, Brian R.; Sauther, Michelle L.; Ungar, Peter S.; O'Mara, M. Teague
<x xml:space="preserve">Abstract</x> Ring‐tailed lemurs (Lemur catta) at the Bezà Mahafaly Special Reserve (BMSR), Madagascar display a high frequency of individuals with notable and sometimes extreme tooth wear. Adult lemurs display a range of tooth wear even among individuals of the same age, but we do not know at what age this variation first appears. This study's goal was to determine whether wear variation occurs in younger wild lemurs. Based on the decade‐long study of ring‐tailed lemur feeding and dental ecology at BMSR, we hypothesized that younger, natal lemurs (under 5 years of age), would display variation in their degree of tooth wear that would correspond to microhabitat differences, given differences in food availability in different troops' home ranges. We also hypothesized that wear would differ between sexes at this young age, given differences in feeding between males and females in this population. Hypotheses were tested using dental topographic analyses using dental impressions collected from known‐aged lemurs across 10 years at BMSR. Results illustrate significant differences in wear‐related tooth topography (i.e., relief and slope, presented here as "occlusal lift") for microhabitat, sex and troop affiliation among lemurs under 5 years of age in this population. Although, all lemurs in this population consume mechanically challenging tamarind fruit, those in more disturbed habitats eat additional introduced foods, some of which are also mechanically challenging. Thus, dietary variation is the likely cause of variation in tooth wear. The wear variation we show at a young age suggests caution when assigning age based on tooth wear in living and fossil primates. These wear‐related tooth shape changes early in life, which reflects sex, habitat variation and levels of anthropogenic disturbance, may potentially impact reproductive fitness later in life. Am. J. Primatol. 76:1037–1048, 2014. © 2014 Wiley Periodicals, Inc.